MARKET SURVEY OF MONDIA WHYTEI (MULONDO) ROOTS IN KAMPALA CITY, UGANDA - Agea, Jacob Godfrey; Katongole, Benard; Katongole, Benard; Waiswa, Daniel; Waiswa, Daniel; Nabanoga, Goretti Nsubuga; Nabanoga, Goretti Nsubuga (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
This study explored the consumers’ and vendors’ perceptions about Mondia whitei roots, in Kampala city, Uganda; determined the marketing margins and the market flow of the roots in the city; documented demand and supply opportunities as well as challenges to marketing of the roots by the vendors. Seventy vendors and 70 consumers of the roots were administered with semi-structured questionnaires. Results showed that M. whytei roots are largely perceived as sexual stimulant, appetiser, flavours for food and drinks, and stimulant for milk production in lactating mothers. Majority of the vendors (74%) and consumers (85%) perceived the trade in the roots as worthwhile. Men and adolescent boys were reported to be the main consumers. Retailers who buy the roots directly from collectors and later sell to consumers dominate the trade. The average price charged per piece and a kilogram of roots increases from collectors, middlemen and to the retailers. The average retail price was US $ 0.12 per piece of the root and US $ 1.50 per kg of the roots. Collectors charged the lowest price (US $ 0.06 and US $ 0.60 per piece and a kilogram of the roots respectively) though their profit margins remained the highest (50%). Several demand and supply opportunities exist for M. whytei roots and these included few sexual stimulant accepted alternatives to M. whytei roots in Kampala city; consumers’ willingness to pay high prices when the roots are scarce, and a large number of M. whytei roots gatherers that could promote the cultivation of this plant for the market. Challenges, such as seasonal low supply of the roots, and unorganised market structure, hamper the trade in M. whytei roots. There is a need for experimental research on efficacies of the perceived uses of the roots reported in this study. The possibility of value addition to the roots sold should be investigated.